HUBUNGAN DIANTARA AUDIENSI DAN MEDIA RADIO UNTUK MENYEBARKAN INFORMASI. - Nevrettia Christantyawati; Aswin Tangdiesak (Jurnal Spektrum Komunikasi, 2021)
The research aims to reveal how the audience both in providing and propagating the traffic information and urban neighborhood experiences. Although nowadays there are abundant of smartphone based-traffic applications, this study explain the media equation theory still work to figure out audiences and media relations. Basically, the information process is very conventional way through Gatekeeper team. The distinguishment is the additional process to broadcast in multiplatform social media such as Facebook and Twitter. This study conducted using depth interview among the audiences, gatekeeper team of Suara Surabaya FM to collect data and the observed the work of informations propagating in social media. The conclusion is that the audience and media relations in sharing and propagating information on the “Kelana Kota” Program on Radio Suara Surabaya FM took place every day and the audience also participated in providing the information they received around Surabaya and the sub urban area. The main crucial finding why the program in propagating urban traffic information does exist amidst the smartphone mobile application is that the radio has power to interact and communicate as human friend. Whilst listening to some informations as well as favourite music plays on, audience can experience well entertained. Compare to smartphone traffic application, the audience prefers rather as additonal information.